Radical orthodoxy: Its ecumenical vision - Ward, G (University of the Free State, 2017)
The first book in the Series Radical Orthodoxy (RO) was not meant to be programmatic or set out to change the direction of modern theology. There are certain shared sensibilities among its authors and, principally, an ecumenical vision. This article sketches the nature of that ecumenical vision that begins with the way in which secularism has enabled Christians to look beyond their own denominational borders and even share resources. This is bottom-up ecumenism nurtured by multiple belonging and a global understanding of Christianities that has helped "de-colonize" theology and rethink political theology. RO, it is argued, can be a resource for the South African de-colonization of Christian theology. In its critiques of modernity and secular reasoning, RO points the way towards doing theology in, through and beyond traditional and disciplinary boundaries - but South Africa has to make it its own.